South Africa : Staff Report for the 2003 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2003 Article IV Consultation highlights that the South African economy performed well in 2002, notwithstanding difficult global economic conditions. Supported by sound macroeconomic management and a highly competitive exchange rate, real GDP growth rose to 3.0 percent in 2002 from 2.8 percent in 2001. However, growth slowed to 1.5 percent in the first quarter of 2003, largely in response to a strong currency appreciation and tight financial conditions. The sharp currency depreciation that occurred in the second half of 2001 provided a major boost to activity during much of 2002.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet